Performance of safflower and linseed intercropping system with different row proportions under rainfed conditions: PERFORMANCE OF SAFFLOWER AND LINSEED INTERCROPPING SYSTEM UNDER RAINFED CONDITIONS - KARALE GANGADHAR; S A BIRADAR; B K DESAI; N ANANDA; K AJITHKUMAR (Journal of Oilseeds Research, 2016)
Field experiment was conducted at Main Agricultural Research Station, Raichur, Karnataka during rabi season of 2015-16 to study the yield performance and economics of safflower and linseed intercropping system with different row proportions. The results revealed that, among various intercropping systems safflower + linseed in 1:2 row proportion recorded significantly higher safflower equivalent yield of 1686 kg/ha followed by safflower + linseed in 1:1 row proportion 1450 kg/ha. The land equivalent ratio was significantly highest in safflower + linseed in 1:2 row proportion (1.20) followed by safflower + linseed in 2:1 row proportion (1.03). Higher net return was recorded in safflower + linseed in 1:2 row proportion (` 23,212/ha) followed by sole linseed (` 19,376/ha) and sole safflower (` 18,979/ha). However, higher B: C was recorded in safflower + linseed (1:2) row proportion (2.22).